Model Infrastruktur Backup Data Menggunakan NAS untuk Menunjang Keberlangsungan Sistem Informasi Perusahaan - Naveliano, Iqbal; Suhendi, Suhendi (DBESTI: Journal of Digital Business and Technology Innovation, 2025)
The rampant cyber attacks that have hit Indonesian cyberspace recently have resulted in data loss in several companies. The cyber attacks that occurred are hazardous to company data. In 2022, the company PT. Global Media Utama Teknologi experienced a ransomware cyber attack that resulted in data loss and caused losses to the company. This incident requires a solution to prevent data loss from occurring again due to cyber attacks or accidents in company operations. In this study, a data backup infrastructure design was implemented at PT. Global Media Utama Teknologi uses several technologies, such as Network Attached Storage (NAS) and backup applications from Acronis Cyber ​​Protect. This study was tested at the end using Black Box Testing, User Acceptance Testing (UAT), Backup Testing, and Restore Testing. The results of the study show that the backup infrastructure design at PT is Global Media Utama Teknologi has run according to user wishes.